KEWENANGAN PRESIDEN DALAM MENETAPKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 2011 - Hartono Hartono (Maleo Law Journal, 2020)
One form of presidential power mandated by the 1945 Constitution of the Republic of Indonesia (1945 Constitution) is to give the President exclusive authority in the field of legislation to establish Government Regulations in lieu of Laws, hereinafter referred to as Perpu, whose procedures and procedures differ from the establishment legal products at normal times. Such a situation gives the President the authority to enact a Perpu, a regulation which in terms of content should be determined in the form of a law, but because of a state of urgency that is forced to be determined in the form of a government regulation. Kata Kunci : Kewenangan. Presiden.